Small-Firm Networks and strategies for consolidation: evidence from the Brazilian context - Wegner, Douglas; Bortolaso, Ingridi Vargas; Zonatto, Patrinês Aparecida França (Review of Business Management, 2016)
Purpose – This study aimed to analyze the strategies adopted by small-firm networks (SFNs) to achieve consolidation. Design/methodology/approach – This study was conducted in two stages with a qualitative approach. The first stage aimed to identify consolidated SFNs in the southern region of Brazil. The second stage consisted of analyzing three case studies to investigate which strategies they adopted to reach consolidation. Findings – The results show four specific strategies implemented by the SFN to expedite their consolidation: adoption of a network administrative organization; hiring of professional managers; a portfolio of services to support network members; and cooperation and merger of SFNs. Originality/value – The analysis of the three consolidated SFNs provides a better understanding of the network development process and the strategies adopted for their evolution.